Studio dal naturale e eclettismo nello 'Schilder-Boeck' di Karel van Mander - Pierguidi, Stefano (Incontri. Rivista europea di studi italiani, 2012)
Naturalism and Eclecticism in Karel van Mander’s Schilder-BoeckA passage in Karel van Mander’s Life of Goltzius is an important, but overlooked, moment in support of the so-called theory of the eclecticism that in seventeenth century art criticism flourished around the Carracci painters – Agostino in particular. In the last century, scholars have often looked at this theory as one in opposition to that of the study from nature. However, men like van Mander or Agucchi thought, instead, that only Caravaggio’s obsessive naturalism was incompatible with the study of sixteenth century painting. Passages from the Schilder-Boeck from the lives of Dürer and Cornelisz, which depend on Vasari’s Lives, clearly confirm this point. The relation between the theory of the eclecticism and the theory of the selection of the ‘Idea del Bello’ from Nature is somewhat implied in van Mander’s book and would go on to be clarified later in the seventeenth century by Bellori and Malvasia.